January effect: The Malaysian experience - Othman Yong, (Penerbit Universiti Kebangsaan Malaysia, 1989)
Past studies in the United States, Canada and Australia indicated the existance of seasonality effect, I.e. "January effect" and "end-of-the-year effect ", due to taxes imposed on the capital gains in these countries. This paper attempted to find out whether or not this conclusion is also true in the case of Malaysla where there IS no tax Iiposed on the capital gains. Overall, iniatial observation showed that the average returns are higher in January compared to other months for 5 out of 6 sectors of the Kuala Lumpur Stock Exchange. However, the F-statlstlc test indicated that the overall differences among these months were not statistically significant, which means there is no seasonality effect in Malaysia. The.t-stallstlc test whIch made a detailed comparison between the average returns In January wah that of other individual month found that, except for a few cases, the average returns in January were not that much different from other months.